Ensuring accurate testing for human immunodeficiency virus in Myanmar - Latt Latt Kyaw; Ikuma Nozaki; Koji Wada; Khin Yi Oo; Htay Htay Tin; Namiko Yoshihara (The World Health Organization, 2015)
Problem Until 2005, the quality of rapid diagnostic human immunodeficiency virus (HIV) testing was not monitored and no regular technical support was provided to hospital laboratories in Myanmar. Approach The national reference laboratory introduced a national external quality assessment scheme. The scheme involved (i) training laboratory technicians in HIV testing and in the requirements of the quality assessment system; (ii) implementing a biannual proficiency panel testing programme; (iii) on-site assessments of poorly-performing laboratories to improve testing procedures; and (iv) development of national guidelines. Local setting In 2011, a total of 422 public hospitals in Myanmar had laboratories providing HIV tests. In addition, private laboratories supported by nongovernmental organizations (NGOs) conducted HIV testing. Relevant changes The scheme was started in 65 public laboratories in 2005. In 2012, it had expanded nationwide to 347 laboratories, including 33 NGO laboratories. During the expansion of the scheme, laboratory response rates were greater than 90% and the proportion of laboratories reporting at least one aberrant result improved from 9.2% (6/65) in 2005 to 5.4% (17/316) in 2012. Lessons learnt National testing guidelines and a reference laboratory are needed to successfully implement quality assurance of HIV testing services. On-site assessments are crucial for all participating laboratories and the only source for insight on the causes of aberrant results; lessons that the reference laboratory can share nationally. Proficiency testing helps laboratory technicians to maintain HIV testing skills by ensuring that they regularly encountered HIV-positive samples.